Dynamic SARS-CoV-2-specific B-cell and T-cell responses induced in people living with HIV after a full course of inactivated SARS-CoV-2 vaccine - Wang, Xiuwen; Yang, Xiaodong; Zhang, Xin; Yan, Hongxia; Jin, Junyan; Ma, Zhenglai; Duan, Junyi; Zhang, Guanghui; Huang, Tao; Li, Yongzheng; Wu, Hao; Zhang, Tong; et al. (Frontiers in Immunology, 2025)
ObjectiveBoth B-cell- and T-cell-mediated immunity are crucial for the effective clearance of viral infection, but little is known about the dynamic characteristics of SARS-CoV-2-specific B-cell and T-cell responses in people living with HIV (PLWH) after a full course of inactivated SARS-CoV-2 vaccination.MethodsIn this study, fifty people living with HIV (PLWH) and thirty healthy controls (HCs) were enrolled to assess B-cell and T-cell responses at the day before the vaccination (T0), two weeks after the first dose (T1), two months after the first dose (T2), the day of the third dose (T3), one month after the third dose (T4), three months after the third dose (T5) and 12 months (T6) after the third dose.ResultsSARS-CoV-2-specific B-cell and T-cell responses were induced in people living with HIV (PLWH), and these responses lasted at least one year after the third vaccine dose. However, the peak frequencies of Spike-specific B-cell and T-cell responses in PLWH were lower than those in HIV-negative controls. In addition, the expansion of activated B cells, memory B cells and plasma cells after primary vaccination was observed, but the percentages of these cells were decreased at T6 and were comparable to those at T0. Additionally, the percentages of activated T cells, exhausted T cells and SARS-CoV-2-specific T cells with enhanced functional activity were increased following the administration of inactivated SARS-CoV-2 vaccine. In addition, PLWH had lower percentages of plasma cells, RBD-specific B cells, circulating Tfh (cTfh) cells and CD38+ cTfh cells, and the percentages of the latter two types of cells were positively correlated with the titer of neutralizing antibodies, indicating these differences may account for the weaker immune responses induced in PLWH.ConclusionThese data suggest that specific B-cell and T-cell responses could be sustained for at least one year after receiving the third vaccination. Our findings emphasize that the weak SARS-CoV-2-specific B-cell and T-cell responses induced in PLWH have implications for clinical decision-making and public health policy for PLWH with respect to SARS-CoV-2 infection.